Good quality of adaptive seismic studies - Roman, V. I. (Geofizicheskiy Zhurnal, 2016)
Energy and material and technical excess of systems and data of observations, which are the base of modern oil and gas seismic exploration, are not well grounded and excessively cost-based. An alternative for the rise of effectiveness and economy of oil and gas seismic exploration is elaboration and application of adaptive technology of seismic studies and technical means of its realization. The necessity appears to have a comfortable and corresponding to the area of application terminological ensuring of adaptive seismic exploration. Determinative quantitative characteristics of the quality of the utmost effective adaptive seismic studies are the spectra of the ratio the signal-noise. Among the names of their analogues examined and possible variants of terminological adoption the most laconic and accentuated to quality is the notion of good quality.